2004
DOI: 10.1111/j.1467-6494.2004.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Personality–Performance Relationships and the Spurious Moderating Effects of Traitedness

Abstract: This article evaluated the validity of two traditional traitedness measures (i.e., standard deviation traitedness measures and global, single-item traitedness measures) and three new traitedness measures (i.e., multi-item, ranking, and facet traitedness measures). Overall, there was poor construct validity for both the traditional and new measures of traitedness. Furthermore, traitedness was a spurious moderator of the relationship between openness to experience and academic performance. Finally, evidence of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(46 citation statements)
references
References 50 publications
2
44
0
Order By: Relevance
“…Moreover, past research assumed that the relationship between personality traits and creativity is linear, whereas recent research on the effects of personality on a number of outcomes (e.g. Cucina & Vasilopoulos, 2004;Le et al, 2011) is increasingly challenging such an assumption. This study contributes to this emerging debate by exploring the non-linear effects of personality on creativity.…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, past research assumed that the relationship between personality traits and creativity is linear, whereas recent research on the effects of personality on a number of outcomes (e.g. Cucina & Vasilopoulos, 2004;Le et al, 2011) is increasingly challenging such an assumption. This study contributes to this emerging debate by exploring the non-linear effects of personality on creativity.…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%
“…Cucina & Vasilopoulos, 2004;Le et al, 2011;Vasilopoulos et al, 2007). Le et al (2011), for instance, determined that both emotional stability and conscientiousness have a curvilinear relationship with task performance, organisational citizenship behaviour, and counterproductive behaviour.…”
Section: The Non-linear Effects Of Personalitymentioning
confidence: 99%
“…Nonlinear (quadratic) effects are notoriously small in magnitude (Ames & Flynn, 2007;Benson & Campbell, 2007;Cucina & Vasilopoulos, 2005;LaHuis, Martin, & Avis, 2005;Le et al, 2011). In addition, past research studying personality and nonlinear effects has produced disparate results (see Le, Robbins, Ilies, Holland, & Westrick, 2011, for a review of conscientiousness and job performance).…”
Section: A Behavioral Threshold Theory Of Nonlinear Effectsmentioning
confidence: 99%
“…Finally, a few other studies focusing on other outcomes have also found curvilinear relationships. Cucina and Vasilopoulos (2005), for example, found evidence of nonlinear relationships between Conscientiousness (inverted U shaped) and Openness to Experience (U shaped) and grade point average. Vasilopoulos, Cucina, and Hunter (2007) also found evidence of quadratic relationships for Conscientiousness and Emotional Stability predicting training performance.…”
Section: Empirical Evidencementioning
confidence: 99%